Insidious : chapter 2 - Wan, James, 1977-; Wilson, Patrick, 1973-; Byrne, Rose; Simpkins, Ty (Culver City, Calif. : Sony Pictures Home Entertainment, 2013)
While trying to recover from their son's demonic possession, the Lamberts discover that evil spirits are still connected to their family.
Originally released as a motion picture in 2013.
Sequel to the film "Insidious" (2010).
Anamorphic wide screen 1.85:1.
Features: Peripheral vision : behind the scenes, Ghostly transformation.
Patrick Wilson, Rose Byrne, Ty Simpkins, Barbara Hershey, Lin Shaye.
MPAA rating: PG-13.
Keywords: Demoniac possession -- Drama; Supernatural -- Drama; Fiction films; Video recordings for the hearing impaired; Thriller films; Feature films; Horror films